Developing a Total Physical Response (TPR)-Based English Module to Enhance Listening-Speaking Skills of Young Learners - Merlin Waruwu; Yunita Tafonao; Arniwati Gulo; Oktoberlianus Zendrato; Fitri Seniawati Halawa; Arif Wahyu Tomosa Halawa; Yaredi Waruwu (Jurnal Pendidikan dan Sastra Inggris, 2026)
In order to address the issues of classroom management, media integration, and listening-speaking progression that teachers at PPA Kramer Hilina'a Gunungsitoli faced with 18 students ages 6 to 9, this research and development (R&D) study created Total Physical Response (TPR)-based English teaching modules using the ADDIE model. The class D English instructor served as the study population. Semi-structured interviews and TPR classroom observations were used to gather data, which was then subjected to content analysis. Three primary needs were identified by the findings: listening-speaking hurdles, current media structuring (PPT, flashcards, videos), and movement classroom management (73% interview codes). The module increased student engagement from 62% (11/18 students) to 89% (16/18 students), command-response frequency from 8 to 21 per session, and verbal repetition from 9/18 to 15/18 students (83%) after it was tested in two class D sessions and validated by experts (score 4.2/5 or 84%). This low-tech lesson can be replicated in PAUDs with limited funding and space, giving non-specialist teachers formal TPR assistance utilizing already-existing resources at no further cost. Single respondent and short trial duration are research limitations; subsequent long-term testing across several PAUDs is advised.